Synthesis and Antimicrobial Activity of Azepine Analogue of Lignan - Singh, Ashok Kumar (Journal of Nepal Chemical Society, 2013)
Diphenylamine (1) was condensed with maleic anhydride (2) in the presence of sodium hydride and dry benzene, 4-N,N-diphenyl amine-4-oxo-2-butenoic acid (3) was achieved. Intramolecular cyclization of compound 3 with PPE afforded 1-phenyl-1H-benzo[b] azepine-2,5 dione (4). DOI: http://dx.doi.org/10.3126/jncs.v29i0.9236 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 44-47 Uploaded date : 12/3/2013